PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID PADA MATERI POLA BILANGAN DI SMP N 11 KOTA BENGKULU - Rahadi Bimansah; Selly Sindiyani; Adinda Dewi Anggraeni; Ratnah Lestary; Teddy Alfra Siagian (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
In the world of rapidly developing technology education, it can open access to even better education, one of which is the development of smartphone technology which is increasingly favored by the wider community, the use of smartphones can be utilized in media development, especially Android-based media, one that can be developed is media for mathematics lessons, one of which is number pattern material. This study aims to describe the media process that is designed, as well as its development based on Android on Number Pattern material, the model applied in this development, namely (Analysis, Design, Development, Implementation and Evaluation) we are familiar with ADDIE. The goal of this model is to make good quality media. In this study, the researchers took test subjects at SMPN 11 Bengkulu City, with a total of 32 students and 5 math teachers. With diverse mathematical abilities. Data was collected using validation sheets, student respondent questionnaires and application trials. This was done to determine the quality of the media being developed, with the hope of fulfilling the criteria of validity and practicality. The results of the mathematics teacher's response as a material and media expert validator in using the application showed a very good category of 19.5%, a good category of 74%, a poor category of 6.5%, and a very poor category of 0%. While the results of student responses as users in using the application